Optimization of Extraction for Antioxidant and Photoprotective Bioactive Compounds From Ulva Rigida - Bayraktar, Oğuz; Toy, Elif; Bicakci, Beyza Tutku; Erdem, Cansu; Sincar, Bahar; Ozdemir, Feyza; Keskin, Melike; Bayraktar, Oguz (Elsevier, 2025)
This study presents the development and optimization of a green extraction bioprocess for Ulva rigida, aiming to efficiently recover bioactive compounds with antioxidant and photoprotective properties using response surface methodology (RSM). A Box-Behnken design evaluated the combined effects of ethanol concentration (0-100 %), solid-to-liquid ratio (20-40 mL g-1), and extraction time (8-24 h) on extraction yield, antioxidant capacity, and sun protection factor (SPF). All variables significantly impacted extract quality, with ethanol concentration being the most influential. Optimal conditions (100 % ethanol, 1:20 ratio, 16 h) yielded an extract with SPF 11.61 and antioxidant activity of 16.91 mg Trolox/g. Preparative thin-layer chromatography (TLC) of the optimized extract produced three bioactive fractions exhibiting up to 2.3-fold higher SPF and 5-fold greater antioxidant activity. Liquid chromatography-mass spectrometry (LC-MS) analysis confirmed selective enrichment of carotenoids and polyphenols. These findings demonstrate the value of statistically optimized, bioactivity-guided extraction in enhancing Ulva-derived ingredients for cosmeceutical use.
Keywords: Marine Bioactives; Ulva Rigida; Sun Protection Factor; Green Extraction; Cosmeceuticals